Happiness, depression and human benevolence beliefs in institutionalized and non institutionalized major adults - Arias, Walter L. (2013)
In this study we analyze the relations between happiness, depression and human benevolence beliefs in a group of major people who live in asylums (24) and others who live with their families (38). We use Lima’s happiness scale, Yesavage’s Geriatric depression scale and Belief in human scale. We found that there were no significant differences between two groups of major adults in depression levels, but in happiness, positive sense of life and satisfaction with life, non institutionalized older adults had higher punctuations than major people who lived in asylums.